Vitamin-D concentrations, cardiovascular risk and events: a review of epidemiological evidence - Grübler, Martin R.; März, Winfried; Grammer, Tanja B. (Reviews in endocrine & metabolic disorders, 2017)
Vitamin D has long been established as an elemental factor of bone physiology. Beyond mineral metabolism, the expression of the vitamin D receptor has been identified throughout the cardiovascular (CV) system. Experimental studies showed beneficial effects of vitamin D on heart and vessels, but vitamin D intoxication in animals also led to hypercalcemia and vascular calcification. Our knowledge has been extended by epidemiological studies that showed that 25-hydroxyvitamin D (25(OH)D) levels are inversely associated with an increased CV risk itself, but also with established CV risk factors, such as arterial hypertension, endothelial dysfunction and atherosclerosis. Conversely, randomized controlled trials could not document significant and consistent effects of vitamin D supplementation on CV risk or events. Potential explanations may lie in differences in reference ranges or the possibility that low vitamin D in CV disease is only an epiphenomenon. In the latter case, the key question is why low 25(OH)D levels are such a strong predictor of health. While we wait for new data, the current conclusion is that vitamin D is a strong risk marker for CV risk factors and for CV diseases itself.